TRENDS IN THE DEVELOPMENT OF RELIGIOUS TOURISM IN THE CARPATHIAN REGION OF UKRAINE - PANKIV, NATALIYA (Herald of Khmelnytskyi National University. Economic sciences, 2022)
The article examines the current state and prospects of religious tourism in the Carpathian region of Ukraine (which includes four regions of Western Ukraine: Lviv, Ivano-Frankivsk, Transcarpathia, and Chernivtsi). The key functions of religious tourism are outlined. The role of sacred objects in religious tourism is defined. The resource base of the region for the development of religious tourism is described. Sacred objects in the context of all regions of the region have been studied and it has been established that religious tourism occupies a worthy place in the Carpathian region. Wooden churches have been found to play an important role in the development of religious tourism in the region. According to research, in the Lviv, Ivano-Frankivsk, Zakarpattia, and Chernivtsi regions of the Carpathian region found about 5,000 monuments of sacred architecture, among which the most numerous are temples. Of particular value among the sacred sites of the Carpathian region are wooden temples, eight of which are inscribed on the UNESCO World Heritage List. It is established that the Lviv region takes the first place; Significantly fewer sacred objects were found in Ivano-Frankivsk and Zakarpattia oblasts, and Chernivtsi oblast ranks last. The obtained results made it possible to identify promising areas for the development of religious tourism in the Carpathian region. Thus, in the Chernivtsi region, the most sacred monuments of national importance are located in Kitsman, Hertsaiv, Zastavniv districts, and the city of Chernivtsi. In the Transcarpathian region: Velykobereznyansky, Volovets, and Beregovo districts. In Ivano-Frankivsk region: in Kosiv, Verkhovyna and Rohatyn districts. Lviv region ranks first in the Carpathian region in the number of sacred monuments. The largest number of facilities falls in the city of Lviv, as well as: the Drohobych, Starosambir, Zhydachiv, and Turkiv districts. It has been established that most sacred monuments of local and national importance are involved in a number of religious and pilgrimage tours, however, much of the resources are not fully used to promote and develop religious tourism in the Carpathian region.